Pentahelix Synergy in Coral Conservation: Restoring Ecological Health and Enhancing Social Trust through CBPR in Prigi Bay - Dwi Ramadya Risqiana Putri; Aulia Nur Febrianti (Fakultas Teknik Universitas Khairun, 2026)
Coral reef ecosystems at Mutiara Beach, Trenggalek, face degradation due to sedimentation and non-environmentally friendly tourism. This study documents a community service initiative using a Community-Based Participatory Research (CBPR) approach to rehabilitate the reef and empower local stakeholders. Through a Pentahelix synergy involving academics, government, security forces (TNI), the private sector, and the community, 3800 coral fragments were successfully transplanted onto 12 iron rack units. Results indicate a significant increase in coral cover and fish populations, alongside a rise in tourism visits, evidenced by high ticket sales. Furthermore, the project established a sustainable “field laboratory” and strengthened social trust combining technical restoration with multi-stakeholder collaboration is vital for long-term marine conservation.